Strategi Pembelajaran Berdiferensiasi Kurikulum Merdeka guna Meningkatkan Motivasi Belajar Siswa Kelas 8 MTs Al-Husna Probolinggo - Asy'ari, Muhammad Ma'ruf; Rohmah, Azida Nur; Mardhiyah, Ainatul (Lembaga Yasin AlSys, 2025)
The low learning motivation of eighth-grade students at MTs Al-Husna Probolinggo, caused by the use of conventional teaching methods and the high activity load in the pesantren (Islamic boarding school) environment, serves as the background for this study. Within the framework of implementing the Kurikulum Merdeka (Merdeka Curriculum), which emphasizes flexibility and responsiveness to student needs, differentiated instruction is considered a relevant strategy to address this issue. This study aims to examine the effectiveness of differentiated instruction in improving student motivation by adjusting the learning process based on individual interests, readiness, and learning profiles. Using a quantitative approach with an experimental design, a total of 24 students were selected as the sample through purposive sampling. The research instrument was a learning motivation questionnaire administered before and after the intervention and analyzed using a paired sample t-test. The analysis results show an increase in the average score from 90.21 to 124.25 with a significance value of 0.000 (p < 0.05), indicating a significant difference before and after the implementation of the strategy. These findings suggest that differentiated instruction is effective in increasing student motivation and creating a more active and enjoyable learning environment. The implication is that this strategy can serve as a practical solution for teachers to enhance student motivation in religious-based educational institutions and contribute to the academic discourse on the implementation of the Kurikulum Merdeka.